2023
DOI: 10.1186/s12890-023-02346-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prognostic value of osteoporosis in hospitalized patients with bronchiectasis

Abstract: Background The risk factors for osteoporosis and its prognostic value in patients with bronchiectasis is not well characterized. We explored the risk factors for osteoporosis and its prognostic impact in hospitalized non-cystic fibrosis bronchiectasis (NCFB) patients in Southeast China. Methods This observational cohort study consecutively enrolled 179 hospitalized patients with NCFB bronchiectasis between 2017 and 2021. The risk factors and the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Additional disorders of the skeletal system, which includes bone and connective tissue, are also produced by mutations in primary cilia genes [84] and are frequently associated with respiratory infections and bronchiectasis. Osteoporosis, which may appear when ciliary genes, such as IFT80, IFT88, or Kif3a, are mutated [84], is considered a risk factor for bronchiectasis [85,86]. Asphyxiating thoracic dystrophy (Jeune's syndrome) may be caused by mutations in ciliary genes such as DYNC2H1 [75], and mutations in DYNC2H1 [87] and in KIAA0753 [88] were present in patients with recurrent respiratory infections.…”
Section: Potential Connections Between Connective Tissue Diseases Cil...mentioning
confidence: 99%
“…Additional disorders of the skeletal system, which includes bone and connective tissue, are also produced by mutations in primary cilia genes [84] and are frequently associated with respiratory infections and bronchiectasis. Osteoporosis, which may appear when ciliary genes, such as IFT80, IFT88, or Kif3a, are mutated [84], is considered a risk factor for bronchiectasis [85,86]. Asphyxiating thoracic dystrophy (Jeune's syndrome) may be caused by mutations in ciliary genes such as DYNC2H1 [75], and mutations in DYNC2H1 [87] and in KIAA0753 [88] were present in patients with recurrent respiratory infections.…”
Section: Potential Connections Between Connective Tissue Diseases Cil...mentioning
confidence: 99%
“…There is little data on how Aspergillus infections affect osteoporosis, but some studies have found a link between osteoporosis and persistent Aspergillus lung infections. This is due to the possibility of persistent inflammation brought on by Aspergillus infections, which can promote bone resorption and reduce bone growth [71]. Additionally, corticosteroids and other antifungal drugs used to treat Aspergillus infections can raise the risk of osteoporosis.…”
Section: Osteoporosismentioning
confidence: 99%